Planning Bibliography Series No. 37 Reorganisation of Planning Commission - Planning Commission (Planning Commission Government of India, 1964)
The document presents a select bibliography examining the reorganisation of the Planning Commission in India, compiling key articles, commentaries, and scholarly discussions. It highlights debates over the Commission’s efficacy, the proposal for an advisory role, and the need for decentralised and modernised planning mechanisms. By cataloging diverse perspectives on policy reform, structural adjustments, and planning strategies, the bibliography provides a comprehensive resource for researchers and policymakers, facilitating an understanding of the historical and contemporary discourse on the Planning Commission’s evolving role in India’s economic development.
Planning Commission-Library New Delhi August 26, 1967/Bhadra 4, 1889
Planning Commission-Library New Delhi August 26, 1967/Bhadra 4, 1889
Keywords: Reorganisation; Economic Policy; Advisory Role; Decentralised Planning; Administrative Reforms; Policy Reform; Planning Mechanisms; Scholarly Debate; India Economy; Bibliography; Stakeholder Participation